(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione SOMMARIO: 1. Due sentenze che rompono un silenzio durato un decennio – 2. La portata del principio affermato dalla sent. n. 52 del 2016: dal riconoscimento del “diritto a negoziare” l’intesa alla (ribadita) insindacabilità dell’atto di avvio delle trattative – 3. Le ragioni poste a base della decisione della Corte – 4. La libertà di culto di fronte alla rinnovata attenzione per le esigenze di “sicurezza” della collettività nella sent. 63 del 2016 – 5. “Eguale libertà” vs “libertà diversamente graduata” – 6. I riflessi della pronunzia n. 52 del 2016 sul problema della qualificazione del gruppo come “confessione religiosa” – 7. Le oscillazioni della Corte in tema di “laicità” e le criticità emergenti del diritto ecclesiastico italiano. The Constitutional Court once again the leading character of the transition processes of the Italian ecclesiastical politics? ABSTRACT: The present essay analyses the impact of the 2016 Constitutional Court judgements n. 52 and n. 63 on the very “identity”of Italian Ecclesiastical Law, which is characterized by the principles of secularism, equal freedom of religious denominations and by a system of agreements aimed at regulating the specifities of the different religious groups. According to the Author, because of the inactivity of the Legislator, the Constitutional Court is compelled to play a substitute role in searching a satisfactory balance between all these elements and the very settlement of some basic trends in Ecclesiastical Law, as such a subject has to face increasingly new challenges and emerging problems in the management of the religious factor.